La fuerza del discurso epidíctico para motivar y tejer comunidad: el caso de profesores y estudiantes de primer semestre de la Universidad Distrital - Montoya Castillo, Mario (Colombian Applied Linguistics Journal, 2014)
The praise and the censure are always present in the classroom rhetoric epideictic speech, particularly when the teacher transmits values. The epideictic speech also contributes to shape the students’ personality, and this is why nowadays, this speech must be taken seriously. Locating this speech in the classroom environment, and thinking of the different ways to praise and to censure is what we call, in this work, the epideictic as valuation and its power to co-build with the others. The political vocation is making the epideictic to become a social laboratory under this rhetoric perspective, where the pedagogy must be also understood as an exchange of emotions. The approach here is to give the concept of the epideictic speech genre in the university education a different meaning, based on an empiric research. The results of the research of two categories of analysis are presented: The Ethos and the Epideictic formulas.